The Legal Nature of Doctor Patient Relationship in Turkish Medical Law - Unver, Yener (Medicine, Law & Society, 2016)
The article discusses the relationship between the physician and the patient through different branches of Turkish Law. The author explains the legal theory of physician (as self-employed as well as employed in hospital) – patient relationship in the limits of legislation and court practices, and gives special emphasis on contemporary open questions in Turkish Law. Special intentions is given also to criminal law, duty to inform, liability and consent. The author presents contemporary constitutional and supreme court decision relating to the Casarean, plastic surgery, burden of proof, compensations…
Keywords: patient; physician; discrimination; criminal law; Turkish law